First industrial application of an open absorption cycle for heat transformation in a district-heating network. (5th April 2005) - Bittrich, Petra; Hebecker, Dietrich; Bergmann, Thomas
The first plant for high temperature utilisation of higher heating value was realised under industrial conditions in a combined heat and power plant. The technology results in an increased heat recovery temperature and a stronger dehumidification of the flue gas. Beyond that, the use of large solution flow within an adiabatic absorber enables to combine gas scrubbing and dehumidifying. Economic aspects of the technology will be discussed, whereby ratio between surplus and investment costs is used as a dimensionless measure of economic efficiency for the evaluation.